2018
DOI: 10.1007/s00394-018-1794-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of diet in females (F1) from prenatally undernourished mothers on metabolism and liver function in the F2 progeny is sex-specific

Abstract: Maternal undernutrition during gestation (F0) improves the metabolic health of second-generation offspring with more beneficial effects in females.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 62 publications
1
3
0
Order By: Relevance
“…Additionally, while the F1 generation trended toward lower BMIs early in development, the F2 generation had higher BMI scores. In other studies considering underweight mothers and the weight gain of their offspring, maternal undernutrition improves the metabolic health of the next generation 52 and can lead to weight gain and obesity in the next generation 53 , much like what we observed in our overweight F2 generation compared to their underweight F1 mothers.…”
Section: Discussionsupporting
confidence: 83%
“…Additionally, while the F1 generation trended toward lower BMIs early in development, the F2 generation had higher BMI scores. In other studies considering underweight mothers and the weight gain of their offspring, maternal undernutrition improves the metabolic health of the next generation 52 and can lead to weight gain and obesity in the next generation 53 , much like what we observed in our overweight F2 generation compared to their underweight F1 mothers.…”
Section: Discussionsupporting
confidence: 83%
“…Based on the above, we can say that there is an alteration in gene expression that results in an elevated regulation of GFAP and inflammatory mediators, in addition to adipokine receptors, due to overweight/obesity [ 34 , 36 ]. These effects are derived from the defensive response of astrocytes to inflammatory action and injury, which also causes their morphological and functional remodeling, which can cause neuronal hypertrophy [ 37 ]. Debarba et al, in studies carried out in rats that at the neonatal level, showed underfeeding as well as overfeeding, which is generally known as neonatal malnutrition, causes morphological changes in the glia in addition to metabolism alterations that lead not only to increased GFAP expression but also increased expression of T cell protein tyrosine phosphatase (TCPTP) and alterations in connexin 30 expression, molecules related to the regulation of proinflammatory cytokines in the hypothalamic astrogliosis.…”
Section: Role Of Astrocytes In the Expression Of Glial Fibrillary Aci...mentioning
confidence: 99%
“…A relationship between malnutrition and chronic diseases has been observed worldwide ( 1 ). Exponential evidence indicates that perinatal environmental factors, such as maternal malnutrition status, promote long-term effects on the metabolic phenotype of offspring ( 2 , 3 ); this process is known as metabolic programming. Epidemiological and experimental studies suggest that early life nutritional programming is associated with a higher risk for the development of cardiometabolic syndrome ( 4 6 ); an impaired capacity to maintain energy balance is not only limited to exposed individuals but also subsequent generations, even though nutritional conditions are favorable ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…Lactation is a window of susceptibility due to the development and maturation of major organs and tissues, which determine the offspring’s metabolic phenotype ( 2 , 15 ). Thus, exposure to undernutrition during this period can affect metabolism and pancreatic function.…”
Section: Introductionmentioning
confidence: 99%